ANALYSIS OF THE EFFECT OF SERVICE QUALITY ON CUSTOMER SATISFACTION AT PT. HONDA PERDANA SUKABUMI: Manajemen pemasaran - ENDANG NARYONO SE (Ekonomedia, 2020)
In the current business era, the competition in the business world is getting tougher. This requires business people to be able to maximize their company's performance in order to compete in the market. one of the factors that make customers satisfied is the quality of service. The quality of this service has an influence on customer satisfaction. Low quality products will run the risk of unfaithful customers. The purpose of this study was to analyze the effect of service quality on customer satisfaction at PT. Honda Perdana Sukabumi. The population in this study were all employees of PT. Honda Perdana Sukabumi. Determination of the sample in this study using total sampling. By paying attention to time, effort, and cost, the researcher determined 25 people as subjects or respondents and found 25 respondents. Together, the variables Reliability (reliability) (X1), Responsiveness (Capability) (X2), Assurance (X3), Emphaty (empathy) (X4), Tangibles (physical form) (X5) have a significant effect on the variable customer satisfaction (Y). Partially the Reliability variable (X1) has a significant positive effect on the customer satisfaction variable if other variables remain in value. Variable Responsiveness (Capability) (X2) partially has a significant effect on customer satisfaction if other variables remain in value. Assurance variable (guarantee) (X3), partially has a significant effect on customer satisfaction variables if other variables remain in value. The variable Emphaty (empathy) (X4) partially does not have a significant effect on the customer satisfaction variable if other variables remain in value. The Tangibles variable partially has a significant effect on the customer satisfaction variable if the other variables remain in value. Assurance variable (X3) is the independent variable which dominantly affects the dependent variable, namely customer satisfaction.